2016
DOI: 10.1089/mdr.2015.0157
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak Caused byblaOXA-72-ProducingAcinetobacter baumanniiST417 Detected in Clinical and Environmental Isolates

Abstract: We characterized an outbreak of imipenem-resistant Acinetobacter baumannii with clinical and environmental isolates from a tertiary care hospital in San Luis Potosi, Mexico. During a 4-month period, a total of 32 nonrepetitive imipenem-resistant clinical isolates of A. baumannii were collected. All isolates were susceptible to colistin and tigecycline and resistant to cefepime, ceftazidime, ceftriaxone, imipenem, and meropenem. Genotyping by pulsed-field gel electrophoresis showed a major clone (A). Multilocus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…With respect to the A. baumannii populations in Mexico, we are adamant that our study could be of paramount importance for future studies tackling the population genomics of this species in this country. Clearly this is not the first study analyzing A. baumannii isolates from Mexico; in fact, over the last decade there have been several studies (Ares et al, 2013 ; Morfin-Otero et al, 2013 ; Alcantar-Curiel et al, 2014 ; Bocanegra-Ibarias et al, 2015 ; Cornejo-Juarez et al, 2015 ; Gonzalez-Villoria et al, 2016 ; Tamayo-Legorreta et al, 2016 ), which have been very useful from a clinical point of view, as they focused on the molecular epidemiology (Morfin-Otero et al, 2013 ; Gonzalez-Villoria et al, 2016 ; Tamayo-Legorreta et al, 2016 ) or the antibiotic resistance profiles of hospital isolates (Ares et al, 2013 ; Alcantar-Curiel et al, 2014 ; Bocanegra-Ibarias et al, 2015 ). However, none of those studies have analyzed the genomic diversity of the isolates in question and, to the best of our knowledge, this is the first study that has addressed the genetic variation within a population of A. baumannii isolates in Mexico at a genome level.…”
Section: Discussionmentioning
confidence: 93%
“…With respect to the A. baumannii populations in Mexico, we are adamant that our study could be of paramount importance for future studies tackling the population genomics of this species in this country. Clearly this is not the first study analyzing A. baumannii isolates from Mexico; in fact, over the last decade there have been several studies (Ares et al, 2013 ; Morfin-Otero et al, 2013 ; Alcantar-Curiel et al, 2014 ; Bocanegra-Ibarias et al, 2015 ; Cornejo-Juarez et al, 2015 ; Gonzalez-Villoria et al, 2016 ; Tamayo-Legorreta et al, 2016 ), which have been very useful from a clinical point of view, as they focused on the molecular epidemiology (Morfin-Otero et al, 2013 ; Gonzalez-Villoria et al, 2016 ; Tamayo-Legorreta et al, 2016 ) or the antibiotic resistance profiles of hospital isolates (Ares et al, 2013 ; Alcantar-Curiel et al, 2014 ; Bocanegra-Ibarias et al, 2015 ). However, none of those studies have analyzed the genomic diversity of the isolates in question and, to the best of our knowledge, this is the first study that has addressed the genetic variation within a population of A. baumannii isolates in Mexico at a genome level.…”
Section: Discussionmentioning
confidence: 93%
“…ST219 infection was observed in a hospital in Japan [10]. The clonal spread of ST417 occurred in one hospital in Mexico, and some novel STs, such as ST758, ST762 and ST777 were also reported [5].…”
Section: Discussionmentioning
confidence: 97%
“…More recently, some researches revealed that Acinetobacter baumannii ST369 was implicated in the outbreak occurred in hospitals of China and Korean, but it was not the dominant ST [5,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, the most formidable persister with clinical relevance is a new arrival to the general lists, Acinetobacter baumannii , which was placed number one on the WHO list of “priority one–critical” bacteria [8]. It is followed by long-challenging Pseudomonas aeruginosa, which is also extremely abundant and has enormous genetic flexibility and adaptability.…”
Section: Antimicrobial Drug Resistance (Amr) Crisis: Can Medicine Stimentioning
confidence: 99%